2020
DOI: 10.1098/rsos.200603
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow in the Antarctic bivalveAequiyoldia eightsii(Jay, 1839) suggests a role for the Antarctic Peninsula Coastal Current in larval dispersal

Abstract: The Antarctic Circumpolar Current (ACC) dominates the open-ocean circulation of the Southern Ocean, and both isolates and connects the Southern Ocean biodiversity. However, the impact on biological processes of other Southern Ocean currents is less clear. Adjacent to the West Antarctic Peninsula (WAP), the ACC flows offshore in a northeastward direction, whereas the Antarctic Peninsula Coastal Current (APCC) follows a complex circulation pattern along the coast, with topographically influenced deflections depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In this case, migration may be facilitated by the Antarctic Peninsula Coastal Current (APCC) and the Antarctic Circumpolar Current (ACC), as described for D. antarctica (see Leiva et al, 2019) and Aequiyoldia eightsii (see Muñoz-Ramírez et al, 2020).…”
Section: Gene Flow Structure and Genetic Diversity Within The D1mpa P...mentioning
confidence: 99%
“…In this case, migration may be facilitated by the Antarctic Peninsula Coastal Current (APCC) and the Antarctic Circumpolar Current (ACC), as described for D. antarctica (see Leiva et al, 2019) and Aequiyoldia eightsii (see Muñoz-Ramírez et al, 2020).…”
Section: Gene Flow Structure and Genetic Diversity Within The D1mpa P...mentioning
confidence: 99%
“…This wide distribution range on both sides of the Drake Passage has given rise to several revisions of its taxonomic status [ 25 ]. Recently, Muñoz-Ramírez et al [ 26 ] highlighted the role of the Antarctic circumpolar current as a biogeographic barrier between the Antarctic Peninsula and South America, confirming the existence of two different species across the Drake Passage, which, according to Martínez et al [ 27 ], have different levels of susceptibility to two major climate change stressors, namely, temperature shifts and hypoxia. González-Wevar et al [ 28 ] suggested the presence of several cryptic species comprising two lineages along the Antarctic Peninsula (5.78% COI p-distance), a third linage in South America (6.5–7.5% COI and 1.2% ITS p-distances) with respect to the Antarctic peninsula, and two additional mitochondrial lineages on Kerguelen Island and the Falkland/Malvinas Islands.…”
Section: Introductionmentioning
confidence: 99%
“…eightsii but emphasize that Antarctic and South American populations are likely different, but closely related species awaiting formal taxonomic recognition. Recently, Muñoz-Ramírez et al (2020) highlighted based on genomic data the role of the Antarctic Circumpolar Current as a biogeographic barrier to larval transport between both continents, preventing or strongly reducing the potential for genetic connectivity between Antarctic and South American Aequiyoldia lineages. A hypothetical crossing of Aequiyoldia across Drake Passage is then more likely to be caused by ships as larvae in ballast water.…”
Section: Introductionmentioning
confidence: 99%